Chondroprotective Mechanism of Eucommia ulmoides Oliv.-Glycyrrhiza uralensis Fisch. Couplet Medicines in Knee Osteoarthritis via Experimental Study and Network Pharmacology Analysis - Wang P; Xu J; Sun Q; Ge Q; Qiu M; Zou K; Ying J; Yuan W; Chen J; Zeng Q; Cui Q; Jin H; et al. (Dove Medical Press, 2023)
Pinger Wang,1- 3,* Jianbo Xu,1,* Qi Sun,4,* Qinwen Ge,2,3 Min Qiu,1 Kaiao Zou,2,3 Jun Ying,3,5 Wenhua Yuan,2,3 Jiali Chen,2,3 Qinghe Zeng,2,3 Qi Cui,1 Hongting Jin,2,3 Chunchun Zhang,1 Fanzhu Li1 1College of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3The First College of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 4Department of Orthopedic Joint Surgery, Hangzhou Fuyang Hospital of TCM Orthopaedics and Traumatology, Hangzhou, People's Republic of China; 5Department of Orthopedic Surgery, the First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunchun Zhang, College of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China, Tel/Fax +86 571-86613684, Email 20081026@zcmu.edu.cn Fanzhu Li, College of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China, Tel/Fax +86 571-86613684, Email lifanzhu@zcmu.edu.cnBackground: Knee osteoarthritis (KOA) is the primary prevalent disabling joint disorder among osteoarthritis (OA), and there is no particularly effective treatment at the clinic. Traditional Chinese medicine (TCM) herbs, such as Eucommia ulmoides Oliv. and Glycyrrhiza uralensis Fisch. (E.G.) couplet medicines, have been reported to exhibit beneficial health effects on KOA, exact mechanism of E.G. nevertheless is not fully elucidated.Purpose: We assess the therapeutic effects of E.G. on KOA and explore its underlying molecular mechanism.Methods: UPLC-Q-TOF/MS technique was used to analyze the active chemical constituents of E.G. The destabilization of the medial meniscus model (DMM) was employed to evaluate the chondroprotective action of E.G. in KOA mice using histomorphometry, μCT, behavioral testing and immunohistochemical staining. Additionally, network pharmacology and molecular docking were used to predict potential targets for anti-KOA activities of E.G., which was further verified through in vitro experiments.Results: In vivo studies have shown that E.G. could significantly ameliorate DMM-induced KOA phenotypes including subchondral bone sclerosis, cartilage degradation, gait abnormality and thermal pain reaction sensibility. E.G. treatment could also promote extracellular matrix synthesis to protect articular chondrocytes, which was indicated by Col2 and Aggrecan expressions, as well as reducing matrix degradation by inhibiting MMP13 expression. Interestingly, network pharmacologic analysis showed that PPARG might be a therapeutic center. Further study proved that E.G.-containing serum (EGS) could up-regulate PPARG mRNA level in IL-1β-induced chondrocytes. Notably, significant effects of EGS on the increment of anabolic gene expressions (Col2, Aggrecan) and the decrement of catabolic gene expressions (MMP13, Adamts5) in KOA chondrocytes were abolished due to the silence of PPARG.Conclusion: E.G. played a chondroprotective role in anti-KOA by inhibiting extracellular matrix degradation, which might be related to PPARG.Graphical Abstract: Keywords: couplet medicines, UPLC-Q-TOF/MS, network pharmacology, cartilage degeneration, knee osteoarthritis, PPARG